"Oliver Was So Drunk with the Philtre of His Power; He Had Grown Corrupt:" Sir Henry Vane's Political Theology. Issue 7 (3rd October 2019) - Lawlor, Pádraig
ABSTRACT: This study examines the theological writings of and contemporary responses to Sir. Henry Vane (1613–1662). An advocate for religious tolerance, Vane was a leading Parliamentarian during the English Civil Wars and worked closely alongside Oliver Cromwell (1599–1658), the Lord Protector of the Commonwealth of England, Scotland, and Ireland. Vane once served on the Council of State that functioned as the government executive during the Interregnum but would clash with Cromwell over issues of governance. When Cromwell dissolved Parliament in 1653, Vane removed himself from power and retired to pen his theological utterances. By employing Vane's, The retired mans meditations, or, The mysterie and power of godliness (1655), I contend that the statesman's political theology positions Cromwell as the archetypal antichrist of the English Interregnum. Drawing on contemporary responses to Vane's theological writing, I also create a cross-sectional religious and intellectual history that illuminates Vane's theological position.